Development of ICT and Tri-N teaching materials for both in-class and online learning - Miftakhul Huda; Betty Kusumaningrum; I Nyoman Arcana; Mohd Syarull Azlan Yaakub (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This research aimed to develop ICT and Tri-N teaching materials suitable for both in-class and online learning environments and assess their feasibility and effectiveness. The study employed the Research and Development (R&D) method with the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The research was conducted at SMA N 5 Yogyakarta, involving class X1 (in-class learning) and X2 (online learning) with a total of 72 students. Data were collected through student response questionnaires and tests. The developed teaching materials included videos, PowerPoint (PPT) presentations, and handouts. The videos were published on YouTube, providing links to specific sub-materials. The validation results indicated high validity, and student response analysis classified the materials as good. Furthermore, a positive and significant correlation between student responses and learning outcomes tests was observed. The developed teaching materials can serve as effective tools for student learning, and it is recommended for teachers to explore similar approaches for other subjects. This study contributes to the growing body of research on digital pedagogy by providing empirical evidence that ICT-integrated Tri-N teaching materials not only improve student learning outcomes but also offer a scalable and adaptable framework for enhancing instructional quality across varied educational contexts.